Behavioral responses of pyrethroid resistant and susceptible Anopheles gambiae mosquitoes to insecticide treated bed net. - Maxwell G Machani; Eric Ochomo; Fred Amimo; Wolfgang R Mukabana; Andrew K Githeko; Guiyun Yan; Yaw A Afrane (PLoS ONE, 2022)
Background Long-lasting insecticidal nets are an effective tool in reducing malaria transmission. However, with increasing insecticide resistance little is known about how physiologically resistant malaria vectors behave around a human-occupied bed net, despite their importance in malaria transmission. We used the Mbita bednet trap to assess the host-seeking behavior of insecticide-resistant Anopheles gambiae mosquitoes under semi-field conditions. The trap incorporates a mosquito netting panel which acts as a mechanical barrier that prevents host-seeking mosquitoes from reaching the human host baiting the trap. Methods Susceptible and pyrethroid-resistant colonies of female Anopheles gambiae mosquitoes aged 3-5 days old were used in this study. The laboratory-bred mosquitoes were color-marked with fluorescent powders and released inside a semi-field environment where a human subject slept inside a bednet trap erected in a traditional African hut. The netting panel inside the trap was either untreated (control) or deltamethrin-impregnated. The mosquitoes were released outside the hut. Only female mosquitoes were used. A window exit trap was installed on the hut to catch mosquitoes exiting the hut. A prokopack aspirator was used to collect indoor and outdoor resting mosquitoes. In addition, clay pots were placed outside the hut to collect outdoor resting mosquitoes. The F1 progeny of wild-caught mosquitoes were also used in these experiments. Results The mean number of resistant mosquitoes trapped in the deltamethrin-impregnated bed net trap was higher (mean = 50.21± 3.7) compared to susceptible counterparts (mean + 22.4 ± 1.31) (OR = 1.445; P<0.001). More susceptible mosquitoes were trapped in an untreated (mean = 51.9 ± 3.6) compared to a deltamethrin-treated bed net trap (mean = 22.4 ± 1.3) (OR = 2.65; P<0.001). Resistant mosquitoes were less likely to exit the house when a treated bed net was present compared to the susceptible mosquitoes. The number of susceptible mosquitoes caught resting outdoors (mean + 28.6 ± 2.22) when a treated bed net was hanged was higher than when untreated bednet was present inside the hut (mean = 4.6 ± 0.74). The susceptible females were 2.3 times more likely to stay outdoors away from the treated bed net (OR = 2.25; 95% CI = [1.7-2.9]; P<0.001). Conclusion The results show that deltamethrin-treatment of netting panels inside the bednet trap did not alter the host-seeking behavior of insecticide-resistant female An. gambiae mosquitoes. On the contrary, susceptible females exited the hut and remained outdoors when a treated net was used. However, further investigations of the behavior of resistant mosquitoes under natural conditions should be undertaken to confirm these observations and improve the current intervention which are threatened by insecticide resistance and altered vector behavior.